2008
DOI: 10.1002/zoo.20181
|View full text |Cite
|
Sign up to set email alerts
|

Estrous state influences on investigative, aggressive, and tail flicking behavior in captive female Asian elephants

Abstract: Females of species that live in matrilineal hierarchies may compete for temporally limited resources, yet maintain social harmony to facilitate cohesion. The relative degree of aggressive and nonaggressive interactions may depend on the reproductive condition of sender and receiver. Individuals can benefit by clearly signaling and detecting reproductive condition. Asian elephants (Elephas maximus) live in social matrilineal herds. Females have long estrous cycles (14-16 weeks) composed of luteal (8-12 weeks) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Further, we found that the frequencies of U-type lip and genital touches were positively correlated with the proximity index, whereas the frequency of S-type lip touches was not, which may suggest that the U-type lip and genital touches are affiliative. This supports previous studies on captive Asian elephants that used trunk tip touches as indicators of affiliative or investigative behaviours (Garaï 1992;Slade-Cain et al 2008;Makecha et al 2012). Similarly, in African elephants, studies have described mouth and genital touches as types of greeting behaviours (Moss 1988;Moss et al 2011).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Further, we found that the frequencies of U-type lip and genital touches were positively correlated with the proximity index, whereas the frequency of S-type lip touches was not, which may suggest that the U-type lip and genital touches are affiliative. This supports previous studies on captive Asian elephants that used trunk tip touches as indicators of affiliative or investigative behaviours (Garaï 1992;Slade-Cain et al 2008;Makecha et al 2012). Similarly, in African elephants, studies have described mouth and genital touches as types of greeting behaviours (Moss 1988;Moss et al 2011).…”
Section: Discussionsupporting
confidence: 78%
“…We found that the pairs that included neonates used U-type genital touches more frequently than the pairs without neonates did. Previous studies on genital touches in Asian elephants have mainly focused on reproductive behaviour (Meyer et al 2008;Slade-Cain et al 2008). However, our results suggest that U-type genital touches may have an additional function unrelated to reproductive behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found different personality traits among the elephants in this study, in regards to interactions with their physical world (Highfill, Fad, Makecha, & Kuczaj, 2013;Yasui et al, 2013). Furthermore, estrous state may affect enrichment use, as estrous state has been shown to influence aggression and investigative behavior (Slade-Cain, Rasmussen, Schulte, 2008). No data is available on the estrous state of the elephants during the current study.…”
Section: Enrichment Usementioning
confidence: 64%
“…Another study of ex situ female African elephants at a single facility showed that dominant females initiated significantly more ''trunk to mouth'' behaviors toward subordinate elephants when the receiving animal was close to ovulation [Leong et al, 2005]. Females in the follicular phase of estrus and particularly those approaching ovulation are likely to release chemical signals, pheromones, from orifices such as the temporal gland, anus and genitals, and receive more trunk touches from conspecifics [Meyer et al, 2008;Slade-Cain et al, 2008]. Because both cycling and noncycling females were observed, behavioral observations in cycling females were not normalized to estrus.…”
Section: Discussionmentioning
confidence: 98%